The Form of Presenting the Sonde Dance Dance at The Malay Series Art Studio in Pekanbaru City - Sella Oktafira Gea; Herlinda Mansyur (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2023)
The purpose of the research is to describe the Presentation Form of Joget Sonde Dance at the Kenduri Riau Event in Anjungan Seni Idrus Tintin Pekanbaru City. This type of research is qualitative and uses the descriptive analysis method. The instrument used is the researcher himself, with support such as stationery, a camera, and a gadget or smartphone. Data collection techniques include literature study, observation, interviews, and documentation. Data analysis was carried out by reducing data, presenting data, and drawing conclusions. The results of the study prove that the Joget Sonde Dance Sanggar Kumpulan Seni Seri Melayu in the Kenduri Riau event at Anjungan Seni Idrus Tintin Pekanbaru City is a creation dance sourced from the traditional Joget Sonde Dance with a non-representational presentation form and only functions as a means of entertainment. The Joget Sonde dance was performed at the Kenduri Riau event on July 17, 2023. The elements of the Joget Sonde Dance presentation form are as follows: (1) Consists of the Sembah Movement, Lenggang Petik Bunga Movement, Melenggang Movement, Pose Movement, Two Elbow Movement, Joget Duck Movement, Jengger Jolo Movement, (2) Using curved and straight line floor patterns totaling 9 patterns; (3) Music accompaniment, namely Gong, Bebano Drum, Violin, and 1 female singer; (4) Dancers totaling 6 female dancers or more; (5) Makeup (beautiful) costumes (kebaya clothes, brooches, long cloth, shawl cloth, cepol bun, rocking flowers, paper flowers, (6) Place of performance on an open stage.